THE GALICIAN DEANERY IN THE STRUCTURE OF THE UKRAINIAN GREEK CATHOLIC CHURCH (END OF THE 18TH – BEGINNING OF THE 21TH CENTURY): A RETROSPECTIVE VIEW - DELIATYNSKYI, Ruslan; MELNYCHUK, Volodymyr (Halych. Scientific work collection, 2023)
In the article, the authors justify the opinion that the study of the problems of the national and religious identity of Ukrainians requires a reference to the institutional history of the Ukrainian Greek-Catholic Church, particularly at the level of its higher and middle-tier organizational structures ‒ dioceses and deaneries, respectively. There is a noticeable growth of scholarly interest in the history of both individual dioceses and deaneries in contemporary historiography. The canonical-legal principles of the transformation of the organizational structure of the UGCC since the time of the Union of Brest were finally determined by the Zamoiskyi Synod of 1720, indicating three components – diocese, deanery, and parish. In the context of the transformations of the organizational structure of the Lviv diocese during the 17th–19th centuries, the place of the Galician vicariate/deanery was gradually outlined at the territorial level. The authors conducted a retrospective analysis of the historical circumstances of the formation and development of the Galician deanery within the structure of the Greek-Catholic Church from 1772 to 2022. For the first time, a scheme of periodization of the history of the Galician deanery based on two criteria – socio-political and religious-church – was formulated, defining the peculiarities of the development of the UGCC structure. The evolution of the structure of the Galician deanery from 1832 to 1944 at the parish level was reconstructed. The composition of the clergy of the Galician deanery at the level of the deanery council, which included the dean, vice-deans, and priests of the deanery, was analyzed. The article characterizes the features of the transformation of the structure of the Galician deanery in the conditions of the «catacomb» Church (1946–1989), during the process of legalization (1989–1991), and the formation of the modern structure of the UGCC (1991–2022). The authors emphasize the special role of the Galician deanery in the structure of the UGCC and the preservation of national and religious self-consciousness, citing examples such as its preservation under the canonical jurisdiction of the Galician Metropolitan in 1891 and the UGCC Patriarch in 2011. The article outlines prospective directions for further research on the history of the Galician deanery of the UGCC, including the reconstruction of the territorial level of the structure and a prosopographic analysis of the clergy.